Ivan Efimov: architect, warrior, master of Irkutsk facades - Анна Кузьмина; Василий Лисицин (Проект Байкал)
The article considers the life and professional activity of Irkutsk architect I. G. Efimov (1910-1947), whose architectural work includes all style trends of the 1930-1940s. Having received architectural education in Leningrad, Efimov came to Irkutsk and became a sought-after specialist. He carried out individual projects and worked on the facades of already constructed buildings. He was a participant of the Great Patriotic War. After the war, he designed the buildings for the Pedagogical Institute of Foreign Languages and the Vostsibugol Trust in neoclassical style. The buildings became iconic for the centre of Irkutsk.